Development Of Interactive E-Modules Based On Video Tutorial Practices Learning Models in Historical Learning Strategies As A Source Of Innovative Learning - Sidiq, Ricu; Najuah, Najuah; Suhendro, Pristi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study aims to produce interactive e-module products based on practical video tutorials of learning models for the History learning strategy course as an innovative learning resource, with innovations containing a collection of multimedia in the form of graphics, text, images, animations that are processed in such a way as to produce movement and movement. equipped with audio so that it seems alive, which is systematically arranged and stores learning messages that can be used to improve the quality and effectiveness of learning. The method used is the research and development method or Research & Development (R&D). To produce a product, test its feasibility, and its effectiveness in accordance with the development objectives. The research was conducted at the Department of History Education batch 2019. The developed interactive e-module has been validated and meets the criteria for good and appropriate learning media to be used in learning, by obtaining a validation value of 85% from material experts and 87.5% from media experts. While the feasibility of each trial ranged from 89.88% for small trials, 89.77% for medium trials, 83.67% for large trials and the effectiveness obtained a value of 81.04%.